2022
DOI: 10.1177/08850666221115348
|View full text |Cite
|
Sign up to set email alerts
|

Indications, Clinical Impact, and Complications of Critical Care Transesophageal Echocardiography: A Scoping Review

Abstract: Background Critical care transesophageal echocardiography (ccTEE) is an increasingly popular tool used by intensivists to characterize and manage hemodynamics at the bedside. Its usage appears to be driven by expanded diagnostic scope as well as the limitations of transthoracic echocardiography (TTE) – lack of acoustic windows, patient positioning, and competing clinical interests (eg, the need to perform chest compressions). The objectives of this scoping review were to determine the indications, clinical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Compared to TTE, TEE has consistently demonstrated its diagnostic superiority with enhanced resolution, multiplane imaging capabilities, and improved visualization of the RA and its contents 11 , 12 , 13 . In the past decade, there has been a noticeable paradigm shift in the application of TEE 14 , 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to TTE, TEE has consistently demonstrated its diagnostic superiority with enhanced resolution, multiplane imaging capabilities, and improved visualization of the RA and its contents 11 , 12 , 13 . In the past decade, there has been a noticeable paradigm shift in the application of TEE 14 , 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…40 In an extensive review of the literature, Prager et al noted that utilization of TEE in the critical care setting resulted in a change of diagnosis in 52% to 78% of patients and a change in management in 32% to 79% of patients examined. 41 They additionally showed that TEE was able to successfully distinguish the etiology of cardiac arrest in 25% to 35% of cases when it was used for this purpose. 41 As shown in Figures 4 A and B, minimal changes occur in the LV dimension in both systole and diastole, respectively, which is indicative of decreased LV function that can be further assessed and quantified using other 2D and 3D echocardiographic measurements.…”
Section: Echocardiographymentioning
confidence: 99%
“…41 They additionally showed that TEE was able to successfully distinguish the etiology of cardiac arrest in 25% to 35% of cases when it was used for this purpose. 41 As shown in Figures 4 A and B, minimal changes occur in the LV dimension in both systole and diastole, respectively, which is indicative of decreased LV function that can be further assessed and quantified using other 2D and 3D echocardiographic measurements. This patient responded to inotropes to increase cardiac contractility and output.…”
Section: Echocardiographymentioning
confidence: 99%
“…Given some of the limitations of TTE and additional benefits of TEE, there is increasing demand for training in TEE competency amongst general intensivists. Evidence suggests that point-of-care TEE in the ICU improves diagnostic yield beyond TTE, often changes management, and basic midesophageal and transgastric views are readily learned by trainees (52, 57). However, TEE does not come without risks.…”
Section: Future Directions: Point-of-care Transesophageal Echomentioning
confidence: 99%
“…Contraindications include significant esophageal disease such as stricture or recent esophageal or gastric surgery. Severe complications may include oropharyngeal bleeding, esophageal bleeding, and esophageal perforation, although these are rare complications and occur in roughly 0.01–0.5% of cases (57, 58).…”
Section: Future Directions: Point-of-care Transesophageal Echomentioning
confidence: 99%